ANALISIS FORECASTING DALAM PERKEMBANGAN KINERJA KEUANGAN PADA BPRS HARTA INSAN KARIMAH CIBITUNG PERIODE 2013-2020 - Lia Hikmatul Aliyah; Purnama Putra (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
This research Analysis Forecasting in the Development of Financial Performance At BPRS Harta Insan Karimah Cibitung Period 2013-2020. Sharia People's Financing Bank Harta Insan Karimah Cibitung is as research object because This bank has a fairly good financial performance every year. By analyzing the existing financial ratios at BPRS Harta Insan Karimah Cibitung that is Return On Asset, Operating Expenses to Operating Income and Net Profit Margin to know the shortcomings in the past to be better in the future. The methode used in this research processing is quantitative method. The data consist of secondary data The data obtained are not directly from additional information or data used in the form of journals, websites, and other data related to research. Data analysis method using trend analysis Least Square Method. Based on the results of the study, it is known that the development of financial ratios in the next five years will begin year 2021-2025 (quarterly) predicted on the ratio Return On Asset (ROA), that is predicted at year 2021 average of 3,99%, year 2022 decreased average of 3,95%, year 2023 decreased average of 3,91%, at year 2024 decreased average of 3,87%, at year 2025 decreased average of 3,83%. While Financial performance Operational burden on Operational Income, that is increasing every year. In the year of 2021 average of 40,28%, at year 2022 increased by 40,92%, at year 2023 increased by 41,56%, at yaer 2024 increased by 42,20%, at year 2025 increased by 42,84%. While Financial performance analysis forecasting Net Profit Margin (NPM), that is predicted at year 2021 average of 17,21%, year 2022 decreased average of 15,73%, year 2023 decreased average of 14,25%, at year 2024 decreased average of 12,77%, at year 2025 decreased average of 12,29%